ELABORATION AND APPLICATION OF GRAPHICAL MODELS TO OPTIMIZE THE RESPONSE TIME TO EMERGENCY SITUATIONS - PEANCOVSCHII, Serghei (Journal of Engineering Science (Chişinău), 2022)
This article presents methods for timing the key milestones and timing of the emergency response. A graphic model is proposed that allows you to determine the stage and time of the response process, regardless of the nature of the ongoing processes manifestation. The model allows a detailed analysis the process effectiveness of responding to various emergencies. And it also allows to determine the boundaries of responsibility areas to optimize management decisions of the response process, increasing its quantitative and qualitative values. The presented mathematical models exclude errors in assessing the effectiveness of the response. The developed mathematical apparatus can be used for effective management of emergency response units.